Characteristics of microwave-induced discharge over a biomass-derived char spherical carrier. (November 2021) - Li, Longzhi; Meng, Bo; Zhang, Yue; Zhang, Lianjie; Cai, Dongqiang; Sun, Jifu; Tan, Yongdong; Song, Zhanlong; Zou, Guifu; Bai, Yonghui
Abstract: In this study, a new method of microwave-induced discharge over biomass-derived char (i.e., bio-char) spherical carriers was proposed. Bio-char spherical carriers were obtained through rational forming. The discharge intensity and temperature increase under discharge were measured to elaborate the quantitative relationship between microwave discharge and the temperature increase. The effect of bio-char properties on microwave-induced discharge was investigated. The results revealed that discharge achieved the highest electric–thermal conversion efficiency of 61.04%, and the heat generation ratio through the discharge in the initial 10 min was up to 69.08%. The graphitisation degree and transmission depth of microwaves can affect discharge intensity. A critical light intensity inducing hot spot effect exists under different working conditions, and exceeding the critical value led to the hot spot effect and a sudden increase in bed temperature, with a corresponding range of 2.48–5.76 V. The maximum temperature under microwave discharge reached 981 °C, with a heating rate of 376.4 °C/min. The method is potential in the field of value-added utilization of bio-char and microwave-promoted chemical processes.